ANALYSIS OF ILLOCUTIONARY ACT IN THE MOVIE “YOU ARE MY HOME” ENGLISH SUBTITLE - Friska Sari Luksiana Hutajulu; Herman Herman (STKIP Persada Khatulistiwa Sintang, 2019)
An utterance to explain how speaker use language to accomplish intended actions and how the hearers infer intended meaning from what is said called as a speech acts. The study of speech act is very important for us because it can make us comprehend what message that discovered in every utterance. According to Austin (1962) suggests that in uttering a sentence, a speaker is generally involved in three level of speech acts, they are locutionary act, illocutionary act, and perlocutionary act. But for this occasion, this research focuses in analyzing Illocutionary Act in the movie “you’re my home” that presented by Evim Sensin. This research used the combination between qualitative and quantitative approach. The research problem will be discussed are: First, What types of Illocutionary acts are found in “You are my home” movie English subtitle? Second, what is the most dominant types of Illocutionary acts used in “You are my home” movie English subtitle? Finally, the purposes of this research are to find out the types of Illocutionary acts and to analyze the most dominant Illocutionary acts produced in “You are my home” movie English subtitle.